An improved and cost reduced quantum circuit generator approach for image encoding applications - Yetis, Hasan; Karakose, Mehmet (Springer, 2022)
The quantum computers in the NISQ era have a limited number of qubits and can produce noisy results. The greater the depth of the circuits, the greater the amount of cumulative noise produced. On the other hand, in order to use classical data in quantum computing, it must be encoded as quantum data. In this study, a new optimum circuit generation algorithm is proposed especially for quantum encoding of data such as images. There are two main optimization methods in the literature for optimizing reversible circuits, ESOP and POE. The proposed algorithm uses both as hybrids, eliminating the disadvantages of both. The proposed algorithm is template-free compared to existing POE methods, and the proposed circuits are easy-to-implement. On the other hand, in cases where the ESOP method does not provide sufficient reduction, the proposed method obtains simpler and optimum circuits. Experimental results show that the proposed method provides an improvement of 40-57% compared to ESOP and derivative methods.
Keywords: Quantum computing; Quantum image encoding; Optimum circuit synthesis; Cost optimization; ESOP; POE